Effect of fertilizer management on growth, yield and cost of sweet corn (Hokido) - Pankaew, Sirikan; Sathien, Rattawadee; Benchasri, Supreeya; Benchasri, Sorapong (Journal of Vocational Education in Agriculture, 2024)
The objective of this experiment was to study the effect of fertilizer management on growth and yield quality of Hokkaido milk sweet corn at Farmer in Phatthalung Province. Sweet corn (hokido) was carried out and was applied fertilizers (treatments) at 5 treatments, 4 replications and 20 plants/replication. Treatment 1) chemical fertilizers were applied 5 g/plant/time of 15-15-15 formulae at 15 Day After Planting (DAP), 15-15-15 formulae at 25 DAP, 46-0-0 formulae at 35 DAP (control). Treatment 2) manures were applied 5 g/plant/time at 15, 25 and 35 days after planting (DAP). Treatment 3) chemical fertilizers were applied 5 g/plant/time of 46-0-0 formulae at 15 DAP, 15-15-15 formulae at 25 DAP, 15-15-15 formulae at 35 DAP. Treatment 4) chemical fertilizers were applied 5 g/plant/time of 46-0-0 formulae at 15 DAP, 15-15-15 formulae at 25 DAP, and 15-15-15 formulae at 35 DAP was applied 3 g/plant. Treatment 5) chemical fertilizers were applied 5 g/plant/time of 15-15-15 formulae at 15 DAP, 15-15-15 formulae at 25 DAP, and 46-0-0 formulae at 35 DAP was applied 3 g/plant. A Completely Randomized Design was planned for each treatment. The results showed that plant height, stem width, and number of leaves in the 4th, 5th, and 6th week after planting were not significantly different (P≥0.05) as well as pod width and pod length. The fresh weight had statistical differences. It was found that treatment 4 showed the highest yield (293.41 g/pod), followed by treatments 3, 1, 5, and 2, with the yield of 289.07, 252.71, 222.44, and 215.55 g/pod, respectively, which found that treatment 4 is the best treatment because it can be adapted to increase the productivity yield and reduce the number of fertilizers. Moreover, It is also the most cost-effective. The cost of fertilizing is only 0.19 baht.